Diseño e implementación de un sistema de energía solar en el laboratorio de energía renovable de la Universidad Técnica de Cotopaxi, para el estudio de los regímenes de captación y almacenamiento de energía renovable. - Coloma Erazo, Carlos Alexander (2017)
In the present project was implemented of an autonomous solar photovoltaic system to supply the energy (lighting and a demonstrative) in the laboratory of renewable energies improving the learning and understanding of issues related to the use of renewable energies as well as analyze their advantages and disadvantages. Analyzing the behavior of a photovoltaic system in real time and to demonstrate the efficiency of the same, through the norms and standards that are incorporated a 24VDC regulator controller, 30A, Morningstar EcoPulse, and an inverter 24VDC and 110 VAC, 1000W)of power. The system account with a bank of batteries made up of two batteries 100Ah, AGM type of deep discharge to 12 VDC connected in series for 24VDC. Photovoltaic modules that supply energy are four each of 85W, 24VDC, 4.67A connected in series and parallel respectively the wiring was carried out with the use of four Copper Conductors THHN N°. Eight AWG wire from the modules to the charge controller, in the laboratory of renewable energies will be installed all computers in this system, for a better view and practice of the students. This solar system implemented allows you to have a day of autonomy of energy supply in the laboratory of renewable energies, in case you do not have a solar radiation during the day.